Review on AI Diet Consultant - Manish Kumar Thakur; Sheela Maharajpet; Deepa Mugad (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
A system that can monitor calories is needed as individuals all over the world are becoming increasingly interested in maintaining a healthy weight, eating more nutritious food, and avoiding junk food. The nutrition from our daily meals can be beneficial in keeping our health. Dietitians and patients can measure and control daily food consumption with the use of the Food Calorie and Nutrition measurement system. The knowledge and information about an individual’s fitness are found on the responsive website that is part of the proposed system. In order to create the website and give it a distinct look, we also used data from gym workout books. The fundamental knowledge of fitness, such as how to stay healthy by exercising and consuming foods high in calories, proteins, and carbs, among other ingredients. Includes user logins for administrators and users as well. A chatbot with artificial intelligence regarding human nutrition is the online artificial dietician. Like an actual dietitian, it serves as a diet consultant. Dietitians are knowledgeable about food’s nutritional content. Based on a person’s schedule, body type, height, and weight, a dietician provides advice. All of this data is also requested and processed by the system from the user. It enquires about the user’s age, height, weight, and number of hours worked. The system stores and processes this data and then calculates the nutrient value needed to fill up user needs.